2012
DOI: 10.1063/1.4753876
|View full text |Cite
|
Sign up to set email alerts
|

Modelling an actively-cooled CPV system

Abstract: We have constructed a 7-node, 1-dimensional model of the heat flow in a water-cooled CPV receiver. The model is validated against data from a module exposed to solar irradiance at various concentrations up to 1,000X at the PETAL solar dish facility at Sede Boqer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Besides, the thermal model of CPVT collectors fairly good matches with experimental data listed in Table 7 [10]. Other subsystems are presented with verified models existed in literature.…”
Section: Model Verificationmentioning
confidence: 76%
See 2 more Smart Citations
“…Besides, the thermal model of CPVT collectors fairly good matches with experimental data listed in Table 7 [10]. Other subsystems are presented with verified models existed in literature.…”
Section: Model Verificationmentioning
confidence: 76%
“…Each selected CPVT, concentrates the light 555 times on a 114 mm  135 mm receiver [10]. Using Mittleman et al equation, the provided electrical power is [5]: h PV is a function of both temperature of cells and the light intensity, however its dependency to intensity is relatively low and thus usually ignored in literature [11,12].…”
Section: Cpvt Collectormentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Lee et al [18] studied the influences of different design parameters on thermal performance of the cooling system for CPV system through CFD simulation. Buonomano et al [19] constructed a 1D model of the heat flow in a watercooled CPV receiver. They found that the model seems to give reasonable results even when the module exposed to the concentration factor up to 1000 suns.…”
Section: Mathematic Descriptionmentioning
confidence: 99%
“…Similarly, the availability of theoretical and experimental studies investigating CPVT performance is scarce. In particular, Buonomano et al (2012;Kribus et al, 2006;Mittelman et al, 2007a;2007b) performed some experimental and theoretical works dealing with CPVT systems. In reference (Mittelman et al, 2007a) presented a novel miniature CPVT based on a dish concentrator (0.95 m 2 ) and a silicon PV cell.…”
Section: Introductionmentioning
confidence: 99%